Complications of Transbrachial Arterial Access for Peripheral Endovascular Interventions. (February 2015) - Treitl, Karla Maria; König, Cosima; Reiser, Maximilian F.; Treitl, Marcus
Purpose: To prospectively assess current limitations and complication rates of the transbrachial access technique for endovascular treatment of peripheral vascular pathologies.Methods: In total, 150 patients (112 men; mean age 66.3±10.0 years) with arterial occlusive disease underwent endovascular therapy via a transbrachial access. Periprocedure data (sheath size, dose area product, fluoroscopy time, and procedure duration) were analyzed. Postprocedure complications of the puncture sites were categorized as minor (local hematoma, pseudoaneurysm, embolization, dissection, minor bleeding) and major (thrombotic occlusion, hematoma requiring surgery, major bleeding, nerve injury).Results: The minor and major complication rates were 14.0% (n=21) and 2.7% (n=4). The most frequent major complication was thrombotic occlusion of the brachial artery requiring surgical treatment (3/150, 2%). There was only one temporary palsy of the median nerve and no stroke. Local hematoma (15, 10%), pseudoaneurysm (3, 2%), or a combination of both (3, 2%) dominated the minor complications. The average dose area product and fluoroscopy time were 12, 752.1±9524.5 cGy*cm 2 and 24.3±18.4 minutes, respectively, though procedure duration was acceptable (121.8±48.9 minutes).Conclusion: Complication rates of the transbrachial access for endovascular treatment of peripheral or visceral artery occlusive disease are tolerably low, making it a safe and an important alternative to the transfemoral access in selected cases, though the radiation exposure is rather high.